Microbial response to long-term spatially stratified phosphorus application in Northeast China - Hou, Liyuan; Han, Bing; Wang, Yixin; Wang, Xiaoli; Shi, Wuliang; Cao, Ning; Zhang, Yubin (Frontiers in Plant Science, 2025)
As a critical factor influencing crop productivity in agricultural ecosystems, phosphorus (P)-fertilizer application can significantly alter soil physicochemical properties. However, the relative efficiencies of different types of spatially stratified P fertilizers and their underlying biological mechanisms remain insufficiently elucidated. In this study, an 8-year field experiment was conducted in a black soil region of Northeast China to compare the effects of five P-fertilization regimes: CK (without P application), FP (100% as basal fertilizer), APP (20% as starter fertilization by ammonium polyphosphate), MAP (20% as starter fertilization by monoammonium phosphate), and CMP (20% as starter fertilization by calcium magnesium phosphate). We systematically investigated the effects of spatially stratified P fertilization on soil physical properties, nutrient accumulation, maize yield performance, and bacterial and fungal community structure. CMP demonstrated the best performance in improving soil aeration and enhancing water infiltration capacity. MAP significantly increased the soil total P content by 18.62% and the soil Olsen-P content by 81.46% compared to those of FP. Both MAP and CMP promoted P uptake in various parts of maize plants, including the roots, straw, and grains. All tested starter P fertilizers improved P use efficiency. Compared to that of FP, the soil P surplus was reduced by 7.52%, 14.74%, and 13.04% under APP, MAP, and CMP, respectively. MAP demonstrated the most pronounced yield-increasing effect. Based on amplicon sequencing (16S rRNA for bacteria, interspacer region for fungi) and microbiome profiling, this study confirms that fungi are more susceptible than bacteria to variations in fertilizer types and application methods. Furthermore, the relative abundance of Tausonia was most significantly influenced by MAP. By enhancing the relative abundance of P-cycling functional genes (gph, phoU), MAP modulated the abundance of dominant microbial taxa such as Acidobacteria and Proteobacteria, thereby significantly improving maize yield. Therefore, in maize cropping systems in the black soil region of Northeast China, optimized P fertilizer selection and application methods can effectively reduce soil P surplus and modulate microbial community structure and functional diversity while maintaining stable crop yields.